Type 1 plasminogen activator inhibitor gene: functional analysis and glucocorticoid regulation of its promoter. - van Zonneveld, A J (1988)
Plasminogen activator inhibitor type 1 is an important component of the fibrinolytic system and its biosynthesis is subject to complex regulation. To study this regulation at the level of transcription, we have identified and sequenced the promoter of the human plasminogen activator inhibitor type 1 gene. Nuclease protection experiments were performed by using endothelial cell mRNA and the transcription initiation (cap) site was established. Sequence analysis of the 5' flanking region of the gene revealed a perfect "TATA box" at position -28 to position -23, the conserved distance from the cap site. Comparative functional studies with the firefly luciferase gene as a reporter gene showed that fragments derived from this 5' flanking region exhibited high promoter activity when transfected into bovine aortic endothelial cells and mouse Ltk- fibroblasts but were inactive when introduced into HeLa cells. These studies indicate that the fragments contain the plasminogen activator inhibitor type 1 promoter and that it is expressed in a tissue-specific manner. Although the fragments were also silent in rat FTO2B hepatoma cells, their promoter activity could be induced up to 40-fold with the synthetic glucocorticoid dexamethasone. Promoter deletion mapping experiments and studies involving the fusion of promoter fragments to a heterologous gene indicated that dexamethasone induction is mediated by a glucocorticoid responsive element with enhancer-like properties located within the region between nucleotides -305 and +75 of the plasminogen activator inhibitor type 1 gene.